PENGGUNAAN BAHAN AJAR TEMATIK PEMBAGIAN UNTUK MENINGKATKAN HASIL BELAJAR DI KELAS IIA MI AHLIYAH II PALEMBANG - Antari, Luvi (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
This study aims to look at improving student learning outcomes in the materials division using a thematic approach based teaching materials. This research is a classroom action research (Claassroom Action Research) with a research subject graders IIA MI Ahliyah 2 Palembang, the second semester of 2014/2015 the number of students 28 people, consisting of 14 male students and 14 female students. This study was conducted by two cycles following the model of a Class Action Research & McTaggart Kemmis models which consists of four stages: planning, implementation, observation, and reflection. The process of collecting data by using observation and tests. Based on this research, the data obtained in the first cycle who scored â¥ 70 there were 17 students with learning completeness percentage amounted to 60.71% of students had reached the indicators of success and the second cycle there are 23 students who reached a value â¥ 70 on the percentage of students learning completeness by 82 , 14% had reached an indicator of success. With the student response rate reached 76.56% in the first cycle and the second cycle reaches 81.25%. It can be concluded that learning by using a thematic approach based teaching materials division performed in this research was effective, because it can improve student learning outcomes in the distribution of matter in class IIA MI Ahliyah II PalembangKeywords: a thematic approach, materials division